Representation of the Indonesian Revolution in the Novel Di Tepi Kali Bekasi by Pramoedya Ananta Toer (History Department, Semarang State University and Historian Society of Indonesia, 2021)
Writing a historical novel is one of an author’s attempts to engage readers emotionally. A history written in the form of a story can prove to be more interesting since it consists of beautifully arranged words that can vividly draw the past. Even though both novels and textbooks issue certain life of communities, historical novels may encourage their readers to see a phenomenon found in history from different perspectives than those of historians’. For example, a romance novel entitled “Bekasi River” was written based on Pramoedya Ananta Toer’s experience of being isolated during the war against the British army. The problem discussed in this article is about the representation of Indonesia’s history during the war of independence in the novel “Di Tepi Kali Bekasi?”. This study used a qualitative content analysis method to understand and present ideas and examine historical elements within the novel. This study used content analysis to describe the details and characteristics of historical narratives. The historical narratives were then compared with historians’ study of the revolution in Bekasi. This comparison will show the relationship between the facts and the fiction found in the novel. There are five patterns of the relationship between those facts and fiction: first, the fictionalization of the characters is an imitation of the reality observed by the author. Second, the historians’ description clarifies the novel’s depiction of historical facts. Third, the historians’ narration is depicted in much more detail in the novel; Fourth, the description of facts in the novel consists of historical facts that historians also revealed; Fifth, the novel brings emotional elements to life, which are difficult to be found in historians’ work.Menulis novel sejarah adalah salah satu upaya penulis untuk melibatkan pembaca secara emosional. Sebuah sejarah yang ditulis dalam bentuk cerita bisa menjadi lebih menarik karena terdiri dari kata-kata yang disusun dengan indah yang dapat menggambarkan masa lalu dengan jelas. Meskipun baik novel maupun buku teks mengangkat kehidupan masyarakat tertentu, novel sejarah dapat mendorong pembacanya untuk melihat fenomena yang ditemukan dalam sejarah dari perspektif yang berbeda dari sejarawan. Sebagai contoh, sebuah novel roman berjudul “Sungai Bekasi” ditulis berdasarkan pengalaman Pramoedya Ananta Toer yang diisolasi selama perang melawan tentara Inggris. Masalah yang dibahas dalam artikel ini adalah tentang representasi sejarah Indonesia pada masa perang kemerdekaan dalam novel “Di Tepi Kali Bekasi?”. Penelitian ini menggunakan metode analisis isi kualitatif untuk memahami dan menyajikan gagasan serta mengkaji unsur-unsur sejarah dalam novel. Penelitian ini menggunakan analisis isi untuk mendeskripsikan detail dan karakteristik narasi sejarah. Narasi sejarah tersebut kemudian dibandingkan dengan studi sejarawan tentang revolusi di Bekasi. Perbandingan ini akan menunjukkan hubungan antara fakta dan fiksi yang ditemukan dalam novel. Ada lima pola hubungan antara fakta dan fiksi tersebut: pertama, fiktifisasi tokoh merupakan tiruan dari realitas yang diamati oleh pengarang. Kedua, deskripsi sejarawan memperjelas penggambaran novel tentang fakta sejarah. Ketiga, narasi sejarawan digambarkan lebih detail dalam novel; Keempat, deskripsi fakta dalam novel terdiri dari fakta sejarah yang juga diungkapkan sejarawan; Kelima, novel menghidupkan unsur-unsur emosional yang sulit ditemukan dalam karya sejarawan.